From steam to IoT-supported cross-border logistics platforms: The social, economic, and logistical impacts of the industrial revolutions - Bányai, Tamás (Advanced Logistic Systems - Theory and Practice, 2024)
This paper explores the economic, social, and logistical impacts of the four industrial revolutions, highlighting how each phase of industrialization transformed societies and economies. The analysis covers shifts in production methods, labor dynamics, and market structures that reshaped economic frameworks and influenced wealth distribution, job creation, and industry specialization. Social consequences, including urbanization, migration, and the development of new social classes, are examined to understand the broader implications on family dynamics, labor rights, and quality of life. The study also addresses the critical role of logistical advancements – from steam transportation to digital supply chains – in expanding markets and driving globalization.